Pengaruh Model Problem Based Learning Berbantuan Media E-Comic Terhadap Hasil Belajar Bahasa Indonesia Pada Siswa Kelas III SD 3 Kalirejo - Maharani, Anisha Peby; Rohim, Dhina Cahya; Prasetiyanto, Moh. Aris; Rahmawati, Septina; Wibowo, Deki (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
The results of observations in class III SD 3 Kalirejo, the application of learning is still lacking in using interesting learning models and media. With the Problem Based Learning (PBL) model assisted by E-Comic media, students can understand learning well. This study aims to determine the effect of using the PBL model assisted by E-Comic media on students' Indonesian language learning outcomes. The research method used is quantitative method in Pre-Experiment Design with the form of One-Group Pretest-Posttest Design. Based on data analysis by testing normality, and Post-test results in the experimental class reached 0.149, followed by a t test which showed a sig value of 0.000, which is smaller than 0.05. This finding confirms that the use of the Problem Based Learning (PBL) model assisted by E-Comic media significantly affects student learning outcomes in Indonesian language subjects in class III. The results of the student response questionnaire to the PBL model assisted by E-Comic media obtained an average of 85% in the very good category. The Problem-Based Learning (PBL) method using E-Comic media creates an effective learning atmosphere and can increase students' interest and motivation to learn, making the learning process interactive and enjoyable.